FEEDBACK 360 DERAJAT UNTUK PENINGKATAN KETERLIBATAN KARYAWAN DALAM APLIKASI HRIS BERBASIS WEB - Wulandari, Sri Hariani Eko; Sagirani, Tri; Nurmatin, Akbar (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
An effective employee performance appraisal system must integrate a comprehensive evaluation approach with strategies to enhance engagement. This study proposes a gamification-based performance appraisal framework combined with 360-degree feedback within a web-based Human Resource Information System (HRIS) application. Gamification elements such as points, challenges, leaderboards, and personalized avatars are incorporated to boost user motivation and interaction. The system was developed using the Waterfall model of the System Development Life Cycle (SDLC). The novelty of this research lies in the systematic integration of gamification into the 360-degree appraisal mechanism, aiming to create a more participatory and interactive evaluation experience. The system’s usability was evaluated using the System Usability Scale (SUS), which yielded an average score of 84.9, categorized as “good.” These results indicate a high level of user acceptance. The findings contribute to the development of adaptive HRIS solutions that not only enhance employee engagement but also support data-driven decision-making in digital human resource management.